Издание "Успехи механики": результаты, анализ, оценки - Чернышенко, И.С.; Рущицкий, Я.Я. (Прикладная механика, 2013)
Запропоновано узагальнену інформацію про шеститомне наукове видання «Успехи механики – Advances of Mechanics». Наведені приклади позитивної оцінки видання провідними світовими науковими установами та вченими. Коротко описаний кожен том. The generalized information on the six-volume edition «Uspiekhi mekhaniki – Advances of Mechanics» is proposed. The examples of positive estimate of edition by the leading world scientific institutions and scholars are shown. Each volume is characterized briefly.